2017
DOI: 10.1002/cbin.10830
|View full text |Cite
|
Sign up to set email alerts
|

Opposing effects of low versus high concentrations of water soluble vitamins/dietary ingredients Vitamin C and niacin on colon cancer stem cells (CSCs)

Abstract: Colorectal cancer is one of the global causes of cancer deaths. Cancer stem cells (CSCs) inside the tumour niche responsible for metastasis and relapses, and hence need to be targeted for cancer therapeutics. Although dietary fibre and lifestyle changes have been recommended as measures for colorectal cancer prevention, no such recommendations are available for using water soluble vitamins as prophylaxis measure for colorectal cancers. High dose of Vitamin C has been proven to selectively kill colon cancer cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 49 publications
2
14
0
1
Order By: Relevance
“…In the present study, NAM showed a strong and significant antiproliferation effect on A375 and SK-MEL-28 melanoma cells, two human melanoma cell lines characterized for high and low aggressiveness, respectively [ 37 ]. NAM was tested in the mM concentration range since similar high concentrations have recently shown activity in melanoma cells [ 23 ] and in colon cancer cells [ 51 ]. In the latter cells low- and high-doses of NAM show opposite effects; micromolar doses appear to be cell-protective while millimolar doses induce cell death, likely related to the oxidative stress [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, NAM showed a strong and significant antiproliferation effect on A375 and SK-MEL-28 melanoma cells, two human melanoma cell lines characterized for high and low aggressiveness, respectively [ 37 ]. NAM was tested in the mM concentration range since similar high concentrations have recently shown activity in melanoma cells [ 23 ] and in colon cancer cells [ 51 ]. In the latter cells low- and high-doses of NAM show opposite effects; micromolar doses appear to be cell-protective while millimolar doses induce cell death, likely related to the oxidative stress [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…NAM was tested in the mM concentration range since similar high concentrations have recently shown activity in melanoma cells [ 23 ] and in colon cancer cells [ 51 ]. In the latter cells low- and high-doses of NAM show opposite effects; micromolar doses appear to be cell-protective while millimolar doses induce cell death, likely related to the oxidative stress [ 51 ]. Cell killing effects of high NAM doses were also observed in C. elegans with defective activity of nicotinamidase PNC-1, where NAM levels increase tenfold [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Opposing effects of low (5-25 μM) and high (100-1000 μM) concentrations of vitamin C were observed in cancer stem cells (CSCs) fractionated from the human colorectal cancer cell line HT-29 [126]. At low concentrations, vitamin C stimulated proliferation of CSCs, but it did not affect nonstem cancer cells and normal fibroblasts.…”
Section: Cancer Stem Cellsmentioning
confidence: 98%
“…La supresión de la respiración debida a los altos niveles de glucosa se conoce como efecto de Crabtree, pero no se sabe todavía si los procesos celulares responsables de esta inhibición (que es muy rápida, ocurre en segundos), son los mismos, o similares, para levaduras y las células cancerígenas (Hagman, et al, 2014;Pfeiffer & Morley, 2014;Hammad, et al, 2016). En estudios recientes se ha confirmado el efecto anticancerígeno del ácido ascórbico en concentraciones altas (Sen, et al, 2017;Xia, et al, 2017;Mastrangelo, et al, 2017), aunque el mecanismo no es todavía claro. No se descarta que ello se deba a la tendencia a generar potencial negativo de la membrana externa por la oxidación de ascorbato, como se muestra en la Figura 1B.…”
Section: Generación Del Potencial De La Membrana Mitocondrial Externaunclassified